EFEKTIVITAS PENERAPAN SANKSI TERHADAP PELAKU PENCEMARAN LINGKUNGAN HIDUP AKIBAT SAMPAH DI KOTA PAREPARE - Asram A.T. Jadda, Sadriyah Mansur, Asrul Hidayat, Wardatul Jannah (FAKULTAS HUKUM UM PAREPARE, 2022)
Cleanliness is a key element in realizing health. In the development and management of waste becomes very important and this cannot be separated from the participation of the community in managing waste. however, at the edge of Mattirotasi Beach, it is found that there is still a behavior of people who throw garbage carelessly. The research with the title